SECURING DEVICES COMMUNITIES IN SPONTANEOUS NETWORKS - Prigent, Nicolas; Bidan, Christophe (International Journal of Computing, 2014)
We define a community as a set of devices able to communicate permanently or erratically and that share a long term trust relation. Small corporate networks or home networks are typical examples of such communities. Historically, the devices of the same community communicated over physically isolated wired networks. They are currently used over spontaneous networks, the characteristics of which have implications, in terms of their security and the mechanisms that can be used to protect such. In this article, we present a fully decentralized service of automated configuration of the security mechanisms dedicated to communities of devices that communicate over spontaneous networks. This service is located on each device of the community and manages information related to the environment of the device and to the security policy. Based on this information, it configures dynamically and automatically the security services available on the device to ensure its security and that of the community to which it belongs.